(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article focuses on developing a methodology for using the Venn diagram and integrating natural sciences in teaching nitrogen-containing organic compounds. Today, an interdisciplinary integration approach is becoming important for enriching students’ theoretical knowledge with practical skills, for an exciting and effective educational process. The article presents a developed method used in a generalized lesson plan so that students can better understand the structure, properties, and biological significance of nitrogen-containing organic compounds in an organic chemistry course, combining biology, physics, and ecology with the Venn diagram in teaching nitrogen-containing organic compounds.